Effect of Formaldeyde Induction of Histopathological Features of The Lungs of Wistar Rats (Rattus Norvegicus) - Anak Agung Ayu Niti Wedayani; Linda Silvana Sari; Eka Arie Yuliyani; Yassa, I Wayan Radityakara Wirasena; Restuningdyah, Novia Andansari Putri (Jurnal Biologi Tropis, 2024)
Formaldehyde, a known carcinogen prevalent in everyday environments, poses significant health risks, particularly through inhalation exposure. This study investigates the histopathological changes in the lungs of Wistar rats induced by formaldehyde at doses of 20, 30, and 40 parts per million (ppm) over a three-month period. The research aims to elucidate the onset of dysplasia, a cellular defense mechanism characterized by abnormal epithelial proliferation, as a response to carcinogenic exposure. Utilizing a post-test only control group experimental design, we observed that increased formaldehyde exposure correlates with a heightened severity of dysplasia, with a statistically significant result (p = 0.002). Our findings indicate that varying doses of formaldehyde lead to differential degrees of dysplasia, underscoring the importance of dose-response relationships in assessing the carcinogenic effects of formaldehyde on lung tissue.